Synthesis of complex intermediates for the study of a dehydratase from borrelidin biosynthesis - Hahn, Frank; Kandziora, Nadine; Friedrich, Steffen; Leadlay, Peter Francis (Beilstein Journal of Organic Chemistry, 2014)
Herein, we describe the syntheses of a complex biosynthesis-intermediate analogue of the potent antitumor polyketide borrelidin and of reference molecules to determine the stereoselectivity of the dehydratase of borrelidin polyketide synthase module 3. The target molecules were obtained from a common precursor aldehyde in the form of N-acetylcysteamine (SNAc) thioesters and methyl esters in 13 to 15 steps. Key steps for the assembly of the polyketide backbone of the dehydratase substrate analogue were a Yamamoto asymmetric carbocyclisation and a Sakurai allylation as well as an anti-selective aldol reaction. Reference compounds representing the E- and Z-configured double bond isomers as potential products of the dehydratase reaction were obtained from a common precursor aldehyde by Wittig olefination and Still–Gennari olefination. The final deprotection of TBS ethers and methyl esters was performed under mildly acidic conditions followed by pig liver esterase-mediated chemoselective hydrolysis. These conditions are compatible with the presence of a coenzyme A or a SNAc thioester, suggesting that they are generally applicable to the synthesis of complex polyketide-derived thioesters suited for biosynthesis studies.
Keywords: aldol reaction; coenzyme A; natural products; pig liver esterase; polyketide biosynthesis; protection groups